Tropical stratospheric zonal winds in ECMWF ERA-40 reanalysis, rocketsonde data, and rawinsonde data - Baldwin, M; Gray, L (2005)
ECMWF ERA-40 reanalysis zonal winds are very close to tropical rocketsonde and rawinsonde (radiosonde and radar wind soundings) observations up to 10 hPa. Above 10 hPa differences increase, although the ERA-40 data provide a good representation of tropical winds up to 2-3 hPa. The amplitudes of the quasi-biennial oscillation (QBO) and the semi-annual oscillation (SAO) derived from ERA-40 data match the rawinsonde and rocketsonde observations up to 2-3 hPa. We conclude that zonal-mean ERA-40 equatorial winds could be used, for most purposes, in place of rawinsonde station observations. Copyright 2005 by the American Geophysical Union.